VALIDITY, RELIABILITY, AND PRACTICALITY OF TEST ITEMS IN AN INTERNET-BASED ENGLISH PROFICIENCY TEST FOR ENGLISH LABORATORY - Emmiyati, Nuri; Asnur, Sardian Maharani; Ahmad, Ahmad (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2024)
One way to evaluate English language skills is through the English Proficiency Test (EPT). This research aimed to develop the Internet-Based English Proficiency Test (IB-EPT) by evaluating its test items' validity, reliability, and practicality. The study followed a research and development approach incorporating qualitative and quantitative methods. The sample consisted of 24 students from UIN Alauddin Makassar. The developed English language test media received positive feedback from the expert validation and field trials. The results revealed that the validity of test items was confirmed, with a coefficient of 0.462 (r table = 0.44). Similarly, using Spearman-Brown product-moment correlation, the test items were reliable, with an index of 0.632, exceeding the critical value of the product-moment table (r table = 0.44). In addition, the students' evaluation of the product’s practicality yielded a score of 83.26%, categorized as “very good,” indicating the product was feasible. It is recommended that higher education policymakers should prioritize equipping campuses with comprehensive facilities, particularly information and communication technology, and provide specialized training for lecturers to develop effective computer-based and online assessments.